1937
DOI: 10.1021/jo01227a005
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Ammonia on Benzoin

Abstract: The action of ammonia on benzoin has been studied previously by Laurent,1 Erdmann,2 and Japp and Wilson.3 These investigators found that the reaction leads to three products-amarone (C28H22N2, m.p. 245°)[also called benzoinimide (Erdmann) and ditolane-azotide (Japp and Wilson)], benzoinam (C28H23N2O, m.p. 190°-220°d epending on the rate SUMMARY 1. The action of ammonia on benzoin in boiling acetic acid yields amarone, dihydroamarone, and 2-methyl-4,5-diphenylglyoxaline.2. Desylamine is assumed to be an interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

1953
1953
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…Their generated pathway was shown in Scheme 2. The results were in agreement with the published literature [18]. …”
Section: Methodssupporting
confidence: 93%
“…Their generated pathway was shown in Scheme 2. The results were in agreement with the published literature [18]. …”
Section: Methodssupporting
confidence: 93%
“…The best results (higher than 80% yield) starting from benzil (4) Different mechanistic pathways have been proposed for this multicomponent reaction having the benzil or benzoin as starting materials. 15,28,33 The proposed rationale by Kokare et al 19 seems to be in accordance with the results in Table 1 (Scheme 2). The authors suggested the initial formation of N,N-ketal (9) under Brønsted acidic catalysis from benzaldehyde (6a) and 2 equivalents of NH 4 OAc (7).…”
Section: Catalystssupporting
confidence: 75%
“…By the proposed mechanistic pathway suggested by Davidson et al, 15 it is clear the aid of acetic acid as a Brønsted acid catalyst. Triaryloxazoles are structurally similar to triarylimidazoles and also have some of their properties, but have been less studied so far.…”
Section: Pyrazine and Triaryloxazolesmentioning
confidence: 93%
See 1 more Smart Citation
“…α-Acyloxyketone has also been used as a simple starting material for the stereoselective synthesis of a variety of different structures, including numerous 1,2-diols [4][5][6][7][8] and heterocyclic systems. [9][10][11] Based on the importance of α-acyloxyketones to chemistry, the development of a concise synthetic method for the preparation of α-acyloxyketone derivatives is important. Although a wide variety of synthetic methods have been investigated to date, 12,13) reports pertaining to the direct synthesis of α-acyloxyketone III by the oxidation of alkyne I are rare, most likely because of the difficulties associated with suppressing the over-oxidation of the product and controlling the regioselectivity of the reaction [14][15][16] (Chart 1).…”
mentioning
confidence: 99%